Determinants of Unmet Need of Married Women in Efforts to Reduce Unmet Need in West Sulawesi - Sukardi Sukardi; Mardioyono Mardioyono; Irma Muslimin; Nurbaya Nurbaya (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Reducing the number of unplanned pregnancies is one way to improve the standard of family planning programs. Unplanned pregnancies due to an unmet need for family planning are one of the factors contributing to the increase in IMR and MMR rates and an increase in the population. This study aimed to analyze what factors are related to the incidence of unmet need for family planning and strategies to accelerate the decline in unmet need for family planning in West Sulawesi Province using the 2021 Family Data Collection data set. The research method used is quantitative with a cross-sectional design on chi analysis-square and quadrant analysis using the 2021 Family Data Collection data set with a total sample of 185,132 couples of childbearing age in the province of West Sulawesi. The study found that education level, employment status, age, and the number of children born alive to couples of childbearing age were significantly related to the incidence of unmet need in West Sulawesi with a p-Value of 0.000 and two districts which were the top priority in accelerating the reduction of unmet need for family planning are Mamuju and Polewali Mandar Regency according to quadrant analysis. The results of this research can provide recommendations for mapping targets and areas to stakeholders to accelerate the reduction of unmet needs for family planning in West Sulawesi.